2016
DOI: 10.1123/ssj.2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Finish Lines, Not Finish Times: Making Meaning of the “Marathon Maniacs”

Abstract: This paper examines how marathoners develop multiple and diverse subjectivities within this distance running space. Specifically, we engage in a case study and critically explore the various ways that a small but growing running group called the “Marathon Maniacs” positions itself within the marathon community. Drawing on Bourdieu’s (1984, 1986, 1990) interdependent concepts of field, habitus, and capital, we uncover the multiple and complex ways that legitimate marathon bodies are constructed within this grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In describing facilitated parkour classes, Wheaton and O’Loughlin (2017) similarly refer to participants with diverse skill levels, including ‘non-sporty’ participants, training together in an atmosphere of mutual support. In Cohen and Hanold’s (2016) study, marathon runners reported that their goal was to run for fun, not time, whilst setting other challenges or simply talking to people and really enjoying the experience. Even the quite capable runners described by Ronkainen et al (2017), while looking to improve their individual athletic performance, were not that interested in running ‘being too serious’ (Ronkainen et al, 2017: 375).…”
Section: Findings: Knowledge Skills and Understandingsmentioning
confidence: 99%
“…In describing facilitated parkour classes, Wheaton and O’Loughlin (2017) similarly refer to participants with diverse skill levels, including ‘non-sporty’ participants, training together in an atmosphere of mutual support. In Cohen and Hanold’s (2016) study, marathon runners reported that their goal was to run for fun, not time, whilst setting other challenges or simply talking to people and really enjoying the experience. Even the quite capable runners described by Ronkainen et al (2017), while looking to improve their individual athletic performance, were not that interested in running ‘being too serious’ (Ronkainen et al, 2017: 375).…”
Section: Findings: Knowledge Skills and Understandingsmentioning
confidence: 99%
“…The only existing study on Marathon Maniacs examined their motivation from a sociological perspective (Cohen & Hanold, 2015). Researchers conducted semi-structured interviews with 30 Marathon Maniac members (16 men, 14 women) at two marathon race expos that have a high attendance from this group (Marathon Maniac Reunion Race held at the Louisiana Marathon in 2014 and the Tacoma City Marathon, held near the Marathon Maniac headquarters).…”
Section: Introductionmentioning
confidence: 99%